Expression of the Long Intergenic Non-Coding RNA (lincRNA) of the NED25 Gene Modulates the microRNA-125b, STAT3, Nitric Oxide, and Procalcitonin Signaling Pathways in Patients with Sepsis - Le, Yuanjie; Chen, Tongen; Xun, Kai; Ding, Tao (Medical science monitor, 2018)
BACKGROUND The aim of this study was to investigate the long intergenic non-coding RNA (lincRNA) of the NED25 gene, and the microRNA (miR)-125b, STAT3, nitric oxide (NO), and procalcitonin (PCT) pathway in sepsis. MATERIAL AND METHODS Seventy-five age-matched and sex-matched patients were divided into three groups: 25 patients with sepsis only; 25 patients with septic shock; and 25 healthy control subjects. Computational analysis and a luciferase assay confirmed that the STAT3 and PCT genes were target genes of miR-125b, whereas the lincRNA of the NED25 gene was validated as an endogenous lincRNA competing with miR-125b for binding to STAT3 and PCT. Real-time polymerase chain reaction (PCR) and Western blot measured the expression of miR-125b, STAT3, and PCT in peripheral blood monocytes (PBM) transfected with miR-125b mimics, miR-125b inhibitors, or small interfering (siRNA). RESULTS The expression of miR-125b, the PCT position ratio, the expression of PCT mRNA and protein were increased when compared with healthy individuals. When compared with the siRNA negative control, miR-125b and the lincRNA of the NED25 gene mimics, as well as STAT3 siRNA significantly downregulated the mRNA and protein expression of STAT3 and PCT; mRNA and protein expression of STAT3 and PCT in cells transfected with miR-125b inhibitors were significantly increased. Intracellular nitric oxide (NO) production was upregulated by miR-125b inhibitors and downregulated by miR-125b mimics or siRNA. CONCLUSIONS Downregulation of the lincRNA of the NED25 gene was associated with sepsis in patients by modulating the signaling pathways downstream of miR-125b/STAT3/PCT/NO signaling pathway.